Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.1 - Radicals and Radical Functions - Exercise Set: 82

Answer

3

Work Step by Step

We are given that $f(x)=\sqrt (2x+3)$. Therefore, $f(3)=\sqrt (2(3)+3)=\sqrt (6+3)=\sqrt 9=3$ We know this, because $3^{2}=3\times3=9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.